2009
DOI: 10.1007/s00595-008-3893-5
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of allogenic blood transfusion in elective cardiac surgery after preoperative autologous blood donation

Abstract: Even with PAD for elective cardiac surgery, patients whose pre-donation hemoglobin value and preoperative platelet count are low may require allogenic blood transfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The report from the STS Workforce on Evidence Based Surgery indicates that numerous studies have identified prolonged CPB time as a risk factor associated with increased transfusions [2], in line with increased blood cell damage and coagulation disorders due to alteration of the coagulation cascade [25]. Swaminathan and colleagues found an association between lowest hematocrit during CPB and increased transfusion [26], while Takami and Masumoto recently indicated that independent factors for allogeneic blood transfusion included preoperative and minimum hemoglobin values during cardiopulmonary bypass [27]. The association between low preoperative hematocrit and increased transfusion is generally confirmed by several studies [2].…”
Section: Discussionmentioning
confidence: 99%
“…The report from the STS Workforce on Evidence Based Surgery indicates that numerous studies have identified prolonged CPB time as a risk factor associated with increased transfusions [2], in line with increased blood cell damage and coagulation disorders due to alteration of the coagulation cascade [25]. Swaminathan and colleagues found an association between lowest hematocrit during CPB and increased transfusion [26], while Takami and Masumoto recently indicated that independent factors for allogeneic blood transfusion included preoperative and minimum hemoglobin values during cardiopulmonary bypass [27]. The association between low preoperative hematocrit and increased transfusion is generally confirmed by several studies [2].…”
Section: Discussionmentioning
confidence: 99%
“…11 Another timely report 12 is on the clinical outcome of perioperative nonpermanent vena cava fi lter placement in the treatment of deep venous thrombosis, a condition the seriousness of which has become increasingly apparent. Other reports include risk factor evaluation for the severely ischemic limb and fi ndings from some basic animal experiments, such as anti-inducible costimulator antibody immunotherapy for cardiac allograft rejection 13 and inhibition of intimal hyperplasia.…”
Section: Heart and Vesselsmentioning
confidence: 99%
“…Screening programmes have substantially reduced the risk for clinically well-known infections such as hepatitis C virus (HCV) and human immunodeficiency virus (HIV), but new viruses with parenteral modes of transmission may create new problems in the future. A benefit of autologous blood predonation (ABP) has been shown for elective coronary artery bypass surgery and cardiac valve operations [8][9][10][11]. Accordingly, we hypothesised that ABP reduces allogeneic transfusion requirement in adults upon re-operation for congenital heart defects.…”
Section: Introductionmentioning
confidence: 96%